PENGARUH RETURN ON INVESTMENT (ROI) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA PT SEMEN BATURAJA TBK - Wahlizah, Lasmi; Yunsepa, Yopi; Malini, Hema (STIE DWI SAKTI BATURAJA, 2024)
The research objective to be achieved in this research is to determine the effect of Return On Investment (ROI) and Return On Equity (ROE) on share prices at PT Semen Baturaja Tbk. Based on the research results, it shows that the multiple linear regression equation is Y= 122.577- 490.535 X1 + 504.939 X2. The correlation value between the Return On Investment (ROI) and Return On Equity (ROE) variables on share prices is 0.489, where the correlation between the independent variable and the dependent variable has a moderate correlation. The coefficient of determination or R Square value is 0.239 (23.9%), this shows the contribution of Return On Investment (ROI) and Return On Equity (ROE) to share prices is 23.9% while the other 76.1% is the contribution of other variables which was not examined in this study. The tcount value of the Return On Investment (ROI) variable is -2.030 < ttable of 2.0345, which means that there is no influence of Return On Investment (ROI) on the share price of PT Semen Baturaja Tbk. Meanwhile, the tcount value for the Return On Equity (ROE) variable is 2.415 > ttable 2.0345, this means that there is an influence of the Return On Equity (ROE) variable on the share price at PT Semen Baturaja Tbk. The Fcount value is 5.182 > Ftable 3.28, which means that there is an influence of the Return On Investment (ROI) and Return On Equity (ROE) variables on the share price of PT Semen Baturaja Tbk.